Laser ablation strontium isotopes and spatial assignment show seasonal mobility in red deer (Cervus elaphus) at Lazaret Cave, France (MIS 6) - Barakat, Sarah; Le Corre, Mael; Willmes, Malte; Cohen, Jessica; Vuillien, Manon; Desclaux, Emmanuel; Britton, Kate (Frontiers in Ecology and Evolution, 2023)
Zooarchaeological analysis is a useful means of exploring faunal palaeoecology, paleoclimate and past human behaviours. The Middle Pleistocene archaeological site Lazaret Cave, located in modern-day Nice, France, features a vast assemblage of faunal remains pertinent to the understanding of early Neanderthal subsistence behaviours as well as red deer (Cervus elaphus) ecology during MIS 6. This pilot study examines materials from archaeological layer UA25, a short-term occupation layer at Lazaret dating to 150,000 years ka, which has revealed 28 early Neanderthal remains as well as thousands of faunal bones, of which red deer and ibex (Capra ibex) are most abundant. Molars from three red deer mandibles and a single ibex were analysed for strontium (87Sr/86Sr) isotopic analysis using laser ablation mass spectrometry to determine animal movements during tooth formation, combined with intra-tooth oxygen (δ18O) isotope analysis to determine seasonality. The isotope data was modelled within a local 87Sr/86Sr isoscape and computational spatial assignment was undertaken to reconstruct potential summer and winter ranges of red deer. Results from this pilot study show seasonal mobility within 20 km of Lazaret, identifying two possible summer and winter ranges for the red deer excavated from UA25. Both possible summer ranges are located at higher elevations further from Lazaret while winter ranges have been assigned to lower elevations closer to the coastline and closer to Lazaret. The ibex shows no 87Sr/86Sr variation throughout the first, second and third molar and the spatial assignment indicates it lived proximal to the site during the period of tooth formation. In addition to providing the first evidence of red deer spatial ecology in southern France during MIS 6, we also infer from the faunal isotope data that hominins at Lazaret Cave were likely hunting red deer in autumn and winter when they were closer to the cave site, while hunting in summer would have required up to 20 km of travel.